The status of Ferruginous Duck Aythya nyroca breeding and wintering in China - Zhao, Xumao; MaMing, Roller (Wildfowl, 2014)
Analysis of data published in the China Bird Report (CBR) and other literature between 1979 and 2013, along with our own field observations, found that the Ferruginous Duck Aythya nyroca now occurs throughout most of China. This contrasts with the situation in 1979, when the species was restricted to a few areas in the west of the country. Ferruginous Duck is predominately a winter visitor to China; up to 850 birds have been counted in Yunnan Province, 4,000 in Sichuan Province, and the wintering population is estimated at 6,000–8,000 individuals. In summer, the breeding population is estimated at 3,000–4,000 individuals (1,500–2,000 pairs), with highest concentrations in Xinjiang (c. 900–1,700 individuals) and Inner Mongolia (750–1,400 individuals). In China, females lay 6–11 eggs, which hatch in early June. The present population in China is likely to have spread from neighbouring central Asia (Kazakhstan, Kyrgyzstan or Mongolia). Since 1980, the climate had gradually changed from warm-dry conditions to a wetter climate in northwest China, making it a more suitable breeding area for this species and providing corridors for their expansion to the east. If the present trend continues, southern China could in the near future become an important wintering area for a duck species that is now increasingly common elsewhere in China.